Impact of maternal prenatal stress by glucocorticoids on metabolic and cardiovascular outcomes in their offspring: A systematic scoping review. - Claudia Eberle; Teresa Fasig; Franziska Brüseke; Stefanie Stichling (PLoS ONE)
Background "Stress" is an emerging problem in our society, health care system as well as patient care, worldwide. Especially by focusing on pre-gestational, gestational but also lactation phases "stress" is to be considered as an own trans-generational risk factor which is associated with adverse metabolic as well cardiovascular outcomes in mothers and their children. Hence, the maternal hypothalamic-pituitary-adrenotrophic (HPA) axis may be stimulated by various "stress" mechanisms as well as risk factors leading to an adverse in utero environment, e.g. by excess exposure of glucocorticoids, contributing to cardio-metabolic disorders in mothers and their offspring. Objective To review the evidence of in utero programming by focusing on the impact of maternal "stress", on adverse cardio-metabolic outcomes on their offspring later in life, by identifying underlying (patho-) physiological mechanisms (1) as well as adverse short and long-term cardio-metabolic outcomes (2). Methods We conducted a systematic scoping review to identify publications systematically including reviews, interventional, observational, experimental studies as well as human and animal model studies. MEDLINE (PubMed) and EMBASE databases and reference lists were searched. Peer-reviewed articles from January 2000 until August 2020 were included. Results Overall, n = 2.634 citations were identified, n = 45 eligible studies were included and synthesized according to their key findings. In brief, maternal hypothalamic-pituitary-adrenotrophic (HPA) axis might play a key role modifying in utero milieu leading to cardio-metabolic diseases in the offspring later in life. However, maternal risk factor "stress", is clearly linked to adverse cardio-metabolic offspring outcomes, postnatally, such as obesity, hyperglycemia, insulin resistance, diabetes mellitus (DM), Metabolic Syndrome (MetS), cardiovascular disease (CD), hypertension, restricted fetal growth as well as reduced birth, adrenal, and pancreas weights. Conclusions Women who experienced "stress" as risk factor, as well as their offspring, clearly have a higher risk of adverse short- as well as long-term cardio-metabolic outcomes. Future research work is needed to understand complex transgenerational mechanisms.